Integrated Analysis of microRNA and mRNA Transcriptome Reveals the Molecular Mechanism of Solanum lycopersicum Response to Bemisia tabaci and Tomato chlorosis virus - Yue, Hao; Huang, Li-Ping; Lu, Ding-Yi-Hui; Zhang, Zhan-Hong; Zhang, Zhuo; Zhang, De-Yong; Zheng, Li-Min; Gao, Yang; Tan, Xin-Qiu; Zhou, Xu-Guo; Shi, Xiao-Bin; Liu, Yong (Frontiers in Microbiology, 2021)
Tomato chlorosis virus (ToCV), is one of the most devastating cultivated tomato viruses, seriously threatened the growth of crops worldwide. As the vector of ToCV, the whitefly Bemisia tabaci Mediterranean (MED) is mainly responsible for the rapid spread of ToCV. The current understanding of tomato plant responses to this virus and B. tabaci is very limited. To understand the underlying mechanism of ToCV with its vector whitefly and the host plant, we adopted a next-generation sequencing approach to decipher miRNAs and mRNAs that are differentially expressed under the infection of B. tabaci and ToCV in tomato plants. Our data revealed that 6199 mRNAs were significantly regulated, and the differentially expressed genes were most significantly associated with the plant-pathogen interaction, the MAPK signaling pathway, the glyoxylate, and the carbon fixation in photosynthetic organisms and photosynthesis related proteins. Concomitantly, 242 differentially expressed miRNAs were detected, including novel putative miRNAs. Sly-miR159, sly-miR9471b-3p, and sly-miR162 were the most expressed miRNAs in each sample compare to control group. Four miRNAs that may play an important role in mediating plant defense pathways were identified. Taken together, the analysis reported in this article lays a solid foundation for further research on the interaction between tomato, ToCV and B. tabaci, and provide evidence for the identification of potential key genes that influences virus transmission in tomato plants.